2003
DOI: 10.4319/lo.2003.48.6.2369
|View full text |Cite
|
Sign up to set email alerts
|

Lateral injection of oxygen with the Bosporus plume—fingers of oxidizing potential in the Black Sea

Abstract: Saline and warm Mediterranean water flowing through the Bosporus Strait maintains a permanent pycnocline with vertical separation of oxic (O 2 ), suboxic (absence of O 2 and H 2 S), and anoxic (H 2 S) zones in the Black Sea. The stable suboxic zone implies restricted vertical mixing of the upper oxic and lower anoxic layers and limited vertical flux of oxygen that cannot balance the upward flux of sulfide. We report data that directly confirm massive lateral injections (Ͼ200 km from the Bosporus) of oxygen-enr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
107
1
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 119 publications
(113 citation statements)
references
References 25 publications
4
107
1
1
Order By: Relevance
“…In contrast to the frequent, strong disruption of the suboxic layer in the southwest stations, the westcentral and northwest stations revealed more stable transitions between oxic and sulfidic waters. And, as a result of the physical gyre circulation (doming of the waters in the central regions; Konovalov et al, 2003), the onset of H 2 S was considerably shallower at the central station ( Fig. 1: 162-16-6, 162-17-2 and 162-17-13) than in the southwest or northwest stations.…”
Section: Article In Pressmentioning
confidence: 94%
See 1 more Smart Citation
“…In contrast to the frequent, strong disruption of the suboxic layer in the southwest stations, the westcentral and northwest stations revealed more stable transitions between oxic and sulfidic waters. And, as a result of the physical gyre circulation (doming of the waters in the central regions; Konovalov et al, 2003), the onset of H 2 S was considerably shallower at the central station ( Fig. 1: 162-16-6, 162-17-2 and 162-17-13) than in the southwest or northwest stations.…”
Section: Article In Pressmentioning
confidence: 94%
“…2, we decided to design and build an in situ chemical analyzer to determine dissolved O 2 and H 2 S and other redox components (Table 1). Deployment of this instrument in 2001 provided in situ voltammetric profiles that helped to document lateral O 2 injection from the Bosporus Plume (Konovalov et al, 2003). This lateral injection suppresses and distorts the suboxic zone and the upper part of the H 2 S onset at stations influenced by Bosporus inflow throughout the southwest Black Sea, as observed in oxygenated waters above 130 m in the southwest (Fig.…”
Section: Oxygen and Sulfide Distributionsmentioning
confidence: 99%
“…This zone was defined by Murray et al (1989Murray et al ( , 1995 as the water layer, where the concentrations of dissolved oxygen and hydrogen sulfide are below the detection limit. In the study of Konovalov et al (2003) these limits have been specified as 30 nmol L −1 for sulfide and 3 µmol L −1 for oxygen. As demonstrated by Stanev et al (2013), Argo floats' observations in the Black Sea equipped with an optode sensor can resolve these low oxygen concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…The vertical diffusion coefficient is very small, which enables one to speculate that the diapycnal diffusion is very low. However, Konovalov et al (2003) reported massive lateral injections of oxygen-enriched waters of the Bosphorus plume into the suboxic and anoxic layers. This could serve as an indication that the isopycnic diffusion could play the major role in propagating tracers' anomalies.…”
Section: Introductionmentioning
confidence: 99%
“…For example, T min was 7.7°C in May 2001 [Konovalov et al, 2003], suggesting no renewal the previous winter.…”
Section: Introductionmentioning
confidence: 99%